2020
DOI: 10.1016/j.jcf.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported alcohol use in the cystic fibrosis community

Abstract: Introduction: Excessive alcohol use (EAU), a harmful pattern of drinking that includes binge drinking and heavy use, occurs in 25% (binge) and 6% (heavy use) of the US population, respectively. Little is known about alcohol use in individuals with cystic fibrosis (CF). The objective of this investigation is to examine alcohol consumption patterns in individuals with CF using a health survey administered from a social media platform. Methods: Individuals with CF, 18 years of age or older, were recruited for par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Of those who reported alcohol use, almost 50% were binge drinkers whereas a further 24% reported constant heavy alcohol intake. This is much higher than in the general population (binge pattern 25%, heavy alcohol use 6% P < 0.001) [23 ▪▪ ]. Although PWCF have the same risk factors for excessive alcohol use as the general population, a concern is the high level of comorbidities in PWCF who admitted excessive alcohol use, including advanced lung disease, CFLD and CFRD [23 ▪▪ ].…”
Section: Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation
“…Of those who reported alcohol use, almost 50% were binge drinkers whereas a further 24% reported constant heavy alcohol intake. This is much higher than in the general population (binge pattern 25%, heavy alcohol use 6% P < 0.001) [23 ▪▪ ]. Although PWCF have the same risk factors for excessive alcohol use as the general population, a concern is the high level of comorbidities in PWCF who admitted excessive alcohol use, including advanced lung disease, CFLD and CFRD [23 ▪▪ ].…”
Section: Epidemiologymentioning
confidence: 97%
“…Until recently, there was limited evidence on the prevalence of harmful alcohol use in cystic fibrosis. In a study of 1000 cystic fibrosis participants, Lowery et al [23 ▪▪ ] reported that 77% of participants were current alcohol users. Of those who reported alcohol use, almost 50% were binge drinkers whereas a further 24% reported constant heavy alcohol intake.…”
Section: Epidemiologymentioning
confidence: 99%
“…In a survey of 952 adults with CF, 729 (77%) consumed alcohol at the time of the survey, and 171 (18%) (n = 171). 7 The patient denied alcoholic drinking over the past 5 months.…”
Section: Case Reportmentioning
confidence: 99%
“…Excessive alcohol use is more frequent in CF patients despite major comorbidities (advanced lung disease, CFLD, or CF‐related diabetes). In a survey of 952 adults with CF, 729 (77%) consumed alcohol at the time of the survey, and 171 (18%) ( n = 171) 7 . The patient denied alcoholic drinking over the past 5 months.…”
Section: Case Reportmentioning
confidence: 99%
“…Heavy alcohol use is defined as 8 or more drinks per week (14 in men) and binge drinking is defined as 5 or more drinks on a day or 4 drinks in a 2‐h period (5 in males). Lowery and colleagues 17 sought to understand alcohol use in adults with CF. In an anonymous survey, 952 PwCF (>18 years), 77% of respondents use alcohol currently.…”
Section: Diagnosismentioning
confidence: 99%